Effect of cognitive stimulation therapy in combination with other intervention modalities on cognitive ability in elderly with cognitive impairment: a quasi-experimental study - Turana, Yuda; Sani, Tara Puspitarini; Prasetya, Virginia Geraldine Hanny; Suswanti, Ika; Konny, Lisye; Halim, Magdalena Surjaningsih; Handajani, Yvonne Suzy (Universa Medicina, 2024)
BackgroundCognitive stimulation therapy (CST) has been proven to be beneficial in improving cognition and quality of life in people with mild cognitive impairment (MCI) and mild dementia (MD). This study investigates the benefit of more frequent exclusively CST intervention compared to less-frequent CST-exercise combination on cognitive ability among elderly people with cognitive impairment. MethodsA quasi-experimental controlled study involving 22 subjects aged = 60 years with cognitive impairment. They were divided into three groups: group A (6 months, weekly CST + exercise sessions, n=13), Group B (3 months, twice-weekly CST-only sessions, n=5), group C (3 months, no intervention, n=4) as control. The Modified Mini Mental State Examination Indonesian Version was used for evaluating the cognitive ability of the elderly subjects. Data were analyzed using one-way Anova and Kruskal-Wallis tests ResultsAll participants completed the study, the majority being female with mean age of 70.43 ± 6.97 years and differences in education level distribution across the three groups. The scores before and after the intervention showed a significant difference in the registration and construction domains (p<0.005). However, there was a greater improvement of the mean difference in cognitive scores in groups A and B compared to the control group, although the difference was not statistically significant (p >0.05). ConclusionA twice-weekly CST-only intervention and a once-a-week CST-exercise combination provide better cognitive improvement than no intervention (control). Therefore, elderly people with cognitive impairment should be encouraged to engage in physical activities, brain training, and group activities for promoting the brain’s ability.